ASSOCIATION OF OBSTRUCTIVE SLEEP APNEA AND BLOOD PRESSURE ON HYPERTENSIVE PATIENT IN DEPOK INDONESIA - Astridivia, Mia; Kuntarti, . (LIFE: International Journal of Health and Life-Sciences, 2017)
Over the past few years, the number hypertensive patients in Indonesia have increased rapidly. Previous studies have investigated that OSA independently is important risk factor of hypertension. In Indonesia, there were still lacks of study between OSA and blood pressure on population-based or clinical-population.The objective of this study was to know the relation of OSA to blood pressure on hypertensive patients. This study design was descriptive correlation with cross-sectional approach on 96 hypertensive patients at one of the community health center in Depok city, who were selected with consecutive sampling technique. The OSA was assessed by using the Berlin questionnaire, blood pressure was assessed by aneroid sphygmomanometer, and anthropometric measurements was assessed by weight scale and stature meter. This study showed that 57,3% subjects had the high risk for OSA. The result of analysis by using the Mann-Whitney test showed that OSA related to systolic blood pressure (p= 0.028; CI95%= 0.000-0.066) but was not related to diastolic blood pressure (p= 0.231; CI95%=0.229-0.416),although there was difference of 10 mmHg, higher on hypertensive patient with high risk OSA. This study showed that OSA related to increasing morbidity of hypertension because its effect on elevated blood pressure.The assessment and management of OSA needs to be implemented in providing health care, in order to increase the quality of life for patients especially on hypertensive patients.